PENGARUH EKSTRAK Azadirachta indica TERHADAP PERTUMBUHAN BAKTERI Enterococcus faecalis PENYEBAB KEGAGALAN PERAWATAN ENDODONTIK (in vitro) - Yoeliani Budisidharta; Sandy Christiono; Ade Ismail A.K; Rama Putranto (Jurnal Medali, 2013)
Enterococcus faecalis is a gram positive bacterium which is commonly found in dental root canal endodontic failure. Neem leaf has several active substances such as flavonoids, tannins and sterols which act as an antibacterial. The purpose of this research is to determine the effect of neem leaf extract on the growth of Enterococcus faecalis in vitro.The research was an experimental research, used the posttest only group design. In this research there were five treatment groups (100%, 80%, 60%, 40% and 20%) and two control groups (control + 2, 5% NaOCl and control – sterile distilled water). The diffusion methods were used with calculates diameter zone inhibition of the Enterococcus faecalis bacteria in media MHA by vertically, horizontally, and longitudinally passing through the disc. This research used statistical analysis of One Way Anova that follwed with LSD Post Hoc test.The results mean of inhibition zone diameter of bacteria of Enterococcus faecalis in the treatment group (100%, 80%, 60%, 40% and 20%) in a row 26,38; 22,77; 19,74; 0; 0 and group control + and control – in a row 17 and 0. The One Way Anova test value obtained p<0, 05 means that there were differences in the effect of the inhibition produced by the neem leaf extract. The Post Hoc test value obtained p < 0,05 in the concentration of 100% with concentration 80% and 60% which means there was a significant difference among Neem leaf extracts.The result of the research showed that extract of neem leaf (Azadirachta indica) has an influence on the growth of bacteria Enterococcus faecalis and there were differences in inhibition zone diameter in a range of concentrations. Keyword : neem leaf extract (Azadiractha indica extract), Enterococcus faecalis, in vitro